The Optical Frequency Standards for the Realization of the Meter. Issue 5 (12th December 2018) - Matus, Michael; Haas, Stefan
Abstract: Optical‐frequency standards with various levels of performance are indispensable in metrology and have many applications from length measurement to atomic clocks and much more. The evolution of optical‐frequency standards has been considerable. Originally introduced as primary realizations for the meter, they have evolved to optical clocks, which surpass the uncertainty and stability of microwave clocks. Herein, the status of the development of optical‐frequency standards as far as length metrology is concerned is reviewed, giving a broad overview of the historical context, as well as an outlook about future evolution. Abstract : The evolution of optical‐frequency standards has been considerable . Originally introduced as primary realizations for the meter, they have evolved to optical clocks, which surpass the uncertainty and stability of microwave clocks. This article gives a broad overview of the historical context and an outlook about future evolution.